2005
DOI: 10.1007/s00441-005-1142-4
|View full text |Cite
|
Sign up to set email alerts
|

The development of a long, coiled, optic nerve in the stalk-eyed fly Cyrtodiopsis whitei

Abstract: In the stalk-eyed fly Cyrtodiopsis whitei (Diopsidae; Diptera), the relatively long optic nerve develops within the tight lumen of a very short eyestalk. Axonal growth is generally considered in terms of path finding, selective fasciculation, and towing. Physical forces that are necessary for axon lengthening are generated either by the growth cone or by the growth of surrounding tissues. Therefore, it is surprising to encounter a loosely coiled nerve apparently lacking any attachments that could allow for pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…(34) A further complication to consider is how placement of the eyes and antennae on the end of long stalks affects neural development. (40,41) For example, how is the growth of the optic nerve connecting the photoreceptors of the eye to the visual centres of the brain coordinated? Further work is clearly needed to characterise the morphogenetic movements involved in disc eversion and differentiation in Drosophila and in stalk-eyed flies.…”
Section: Phylogenetic Backgroundmentioning
confidence: 99%
“…(34) A further complication to consider is how placement of the eyes and antennae on the end of long stalks affects neural development. (40,41) For example, how is the growth of the optic nerve connecting the photoreceptors of the eye to the visual centres of the brain coordinated? Further work is clearly needed to characterise the morphogenetic movements involved in disc eversion and differentiation in Drosophila and in stalk-eyed flies.…”
Section: Phylogenetic Backgroundmentioning
confidence: 99%
“…To do this, we looked into the imaginal development of the stalk‐eyed flies and compared it to that of Drosophila . It has been reported that the stalk‐eye like pattern results from the extension of the optic vesicle (Buschbeck et al, ; Buschbeck & Hoy, ). It is interesting how this optic vesicle extension and lateral extension from the head contribute toward the generation of final stalk eye phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Most flies have characteristic compound eyes and antennae on their head, but the stalk‐eyed flies have their eye located at the end of long lateral extension, or stalks. Unlike other stalk‐eye flies where only the eye is located on the stalk, the stalk‐eyed fly from the Diopsidae family have the antenna, eye and optic lobe located at the end of the stalk (Buschbeck & Hoy, ; Buschbeck, Roosevelt, & Hoy, ). The “stalk‐eyed” morphology is a dramatic deviation from other dipterans, including Drosophila (Buschbeck & Hoy, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, doubtful if the Malaysian specimens are really C. whitei. Extensive uses of laboratory-reared C. whitei in behavioral (Lorch et al 1993;Wilkinson et al 1998;Al-Khairulla et al 2003), physiological (Burkhardt & de la Motte 1983;Buschbeck & Hoy 2005) and genetic studies (Wilkinson et al 1997;Wilkinson & Sanchez 2001) has made this species name well known as an experimental object for molecular and behavioral studies of stalked-eyed flies in general.…”
Section: Introductionmentioning
confidence: 99%